Prognostic significance of extranodal extension in oral cavity squamous cell carcinoma with occult neck metastases. Issue 3 (March 2021) - Mamic, M.; Lucijanic, M.; Manojlovic, L.; Muller, D.; Suton, P.; Luksic, I.
Abstract: A grade of extranodal extension (ENE) may advance risk stratification related to survival in patients with metastatic oral cavity squamous cell carcinoma (OCSCC). Pathological examination of 174 OCSCC patients who were primarily surgically treated with tumour resection and elective neck dissection was performed. Data of ENE presence, its extent (in millimetres), patients and tumour characteristics were statistically analysed with respect to disease-free survival (DFS) and overall survival (OS). Ninety patients (51.7%) were identified with occult nodal disease, with 41 patients (23.6%) presenting with ENE. Receiver operating characteristics (ROC) curve analysis set the threshold at 1.9 mm as an optimal ENE cut-off regarding both DFS and OS. Patients were divided by extent into minor ENE (≤1.9 mm) and major ENE (>1.9 mm) subgroups. The subgroup with minor ENE had significantly higher DFS and OS rates compared with major ENE. ENE cut-off threshold at 1.9 mm discriminates low and high-risk subgroups of patients with occult OCSCC in terms of DFS and OS.